Observer agreement in the grading of oral epithelial dysplasia - Brothwell DJ, Lewis DW, Bradley G, Leong I, Jordan RCK, Mock D, Leake JL. (Blackwell Synergy, 2003)
To determine the extent of observer agreement in diagnosis of oral epithelial dysplasia (OED).